Building a Brand and Telling a Story in Perpetual Crisis: Launching a Sustainable Archives Marketing Strategy. Issue 3 (3rd July 2018) - Cline, Tyler; Marcusse, Molly
Abstract : Column description. The Marketing column features essays about a variety of creative and innovative marketing strategies used to highlight collections or promote services in all types of libraries. Its purpose is to provide real examples of how libraries are using marketing and outreach techniques in interesting ways. The column offers practical insight from libraries engaged with marketing. In addition to marketing, the column also features essays on successful programs and events that promote the library. Readers are invited to suggest topics or projects by contacting the column editor, Katy Kelly. Abstract : The American Heritage Center at the University of Wyoming began serious efforts to launch a marketing strategy in 2016, just as the University was hard-hit by a significant funding deficit. The marketing committee was tasked with modernizing and leading marketing efforts. Their focus was incentivizing faculty and staff colleagues to participate in the creation of effective marketing content through social media and other channels. Despite low workplace morale, unfilled positions, University instability, and turnover on the committee itself, the American Heritage Center has implemented a new marketing structure while working with limited financial and human resources.